(untitled) (Nigerian Journal of Technology, 2016)
One of the shortcomings of solar disinfection of water (SODIS) is the absence of a feedback mechanism indicating treatment completion. This work presents the development of an automated batch-process water disinfection system aimed at solving this challenge. Locally sourced materials in addition to an Arduinomicro processor were used to control the algorithm of the water disinfection system. A comparison of solar radiation sensing accuracy of the system to the Campbell Stokes instrument using student’s t-test showed no significance difference between the two data sets at p=0.05. Test conducted with Escherichia Coli spiked water shows that a 6 log reduction in CFU/ml was achieved within 15 minutes for an average global solar irradiance of 400 W/m2. The system disinfected 11 litres of water in a day for solar radiation of 8.5 MJ/m2/day and Escherichia coli concentration not exceeding 106 CFU/ml. http://dx.doi.org/10.4314/njt.v36i1.35